KEHIDUPAN SOSIAL EKONOMI ETNIS JAWA DI DAERAH PERTAMBANGAN PT. SEMEN PADANG KELURAHAN BATU GADANG KECAMATAN LUBUK KILANGAN KOTA PADANG (1970-1998) - Rahayu, Fetria Sri; Husnita, Linda; Aziz, Zulkifli (Pendidikan Sejarah, 2013)
ABSTRACTÂ This paper is a study of the socio economic describing the social and economic life of Javanese Ethnic in the Batu Gadang Village after the PT. Semen Padang displacing the Java Village that used to be near the factory Indarung I and is now a factory area Indarung II to Indarung V. The purpose of this research is to explain the background of the arrival of Javanese Ethnic in the PT. Semen Padang Mining Batu Gadang Village Lubuk Kilangan District Padang, and describe the socio economic life of the community in the area of Java Ethnic PT. Semen Padang Mining Batu Gadang Village Lubuk Kilangan District Padang Year 1970-1998. This thesis uses a historical method consists of four stages . The first phase of the heuristic, the second phase is the source of criticism, the third stage is the interpretation of the facts, and the fourth stage is to do the writing in the form of scientific papers in the form of thesis. The result showed that the social conditions in the area of Java Ethnic PT . Semen Padang Mining Batu Gadang Village Lubuk Kilangan District Padang is very good , cohesiveness and mutual respect is a fundamental principle for them in life, not only against fellow Javanese Ethnic, Minang Ethnic as it is against the natives. Public relations is seen by the formation of an association named âTri Mulyo Mulyoâ. While the economic life of the people are Javanese Ethnic in the middle class because many of them already have their own business, either in the field or home based business industry. From the results of this study concluded that Javanese Ethnic in Batu GadangVillage is a minority, but they can carry out their role properly in everyday life . Social life and high morale, diligent, efficient, and creative, they are able to develop to meet social and economic demands.Â Â Â Â Â Keywords: Javanese Ethnic, Mining, Social Economic Life